Earning Moderates the Influence of CAR, NPL, and BOPO on Company Value in Conventional Banks Listed on the IDX for the 2020-2022 Period - Miranti, Rika Sherly; Walia, Ana Robi; Haris, Abdul (Devotion : Journal of Research and Community Service, 2024)
The goal of research on traditional commercial banks listed on the Indonesia Stock Exchange (IDX) is to use earnings as a moderator to ascertain the impact of the capital adequacy ratio (CAR), non-performing loan (NPL), and BOPO on the value of the company. Variables This study uses a quantitative approach and sample data collection through purposive sampling. The samples obtained for this study are 69 samples that meet the standards of the Indonesia Stock Exchange (IDX) and financial statements for the 2020-2022 period. Classical hypothesis testing and moderate regression analysis (MRA) methods were used to analyze the results of this study. The results showed that the Capital Adequacy Ratio (CAR) did not have a significant effect on the value of the company, and non-performing loans (NPL) did not have a significant effect on the value of the company and operating costs. (BOPO) does not have a significant influence on the value of the company. Capital Adequacy Ratio (CAR) can be changed and affect company value, profit cannot moderate the impact of non-performing loans (NPL) on company performance Product value cannot reduce Operating Costs and Operating Income (BOPO) to company value.